1997
DOI: 10.1074/jbc.272.39.24247
|View full text |Cite
|
Sign up to set email alerts
|

Carbamoylation of Brain Glutamate Receptors by a Disulfiram Metabolite

Abstract: Considerable effort has been devoted to discovery of glutamate antagonists (1, 2) in recent years, due to increasing evidence linking glutamate excitotoxicity to various neurological disorders (3). Unfortunately, while known antagonists can provide neuroprotection, excessive action of these classical blocking agents can obtain undesirable side effects (1, 2). To minimize these undesirable side effects, modification of the redox modulatory sulfhydryl groups of the glutamate receptor has been suggested as a poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 28 publications
(34 reference statements)
1
64
0
Order By: Relevance
“…Several studies have described a rapid modification of cerebral gene expression (at both mRNA and protein levels) in mice subjected to intraperitoneal NMDA injection (Nagendra et al, 1997;Chung et al, 2000;Taniura et al, 2007). To validate our in vitro findings, we evaluated the expression of KPI-APP in cortex of NMDA-treated mice by a single intraperitoneal injection.…”
Section: Memantine Inhibits Cortical Induction Of Kpi-app Expression mentioning
confidence: 99%
“…Several studies have described a rapid modification of cerebral gene expression (at both mRNA and protein levels) in mice subjected to intraperitoneal NMDA injection (Nagendra et al, 1997;Chung et al, 2000;Taniura et al, 2007). To validate our in vitro findings, we evaluated the expression of KPI-APP in cortex of NMDA-treated mice by a single intraperitoneal injection.…”
Section: Memantine Inhibits Cortical Induction Of Kpi-app Expression mentioning
confidence: 99%
“…However, recently we have shown that the active metabolite of disulfiram, DETC-MeSO, not only inhibits acetaldehyde dehydrogenase but also partially blocks glutamate receptors [155]. Furthermore, DETCMeSO is quite effective in preventing seizures induced by NMDA or hyperbaric conditions [155]. Additionally disulfiram has been shown to markedly enhance the anticraving activity of acamprosate [14], suggesting that DETC-MeSO may also have anti-craving activity.…”
Section: Ethanol and Nmda Receptorsmentioning
confidence: 99%
“…S-methyl N,N-diethylthiolcarbamate sulfoxide (DETC-MeSO), the active metabolite of disulfiram, has recently been shown to exert an antagonistic effect on brain glutamate receptors [21]. It is also possible that the clinical efficacy of disulfiram in the treatment of alcoholism is due, at least in part, to its effect on glutamate receptors.…”
Section: Detc-meso and Neuroprotectionmentioning
confidence: 99%